Enhanced Synthesis of Metal‐Organic Frameworks on the Surface of Electrospun Cellulose Nanofibers[a]. Issue 9 (9th March 2015) - Laurila, Elina; Thunberg, Johannes; Argent, Stephen P.; Champness, Neil R.; Zacharias, Savannah; Westman, Gunnar; Öhrström, Lars
<x xml:space="preserve">Abstract</x> This study reports the in situ crystal growth of HKUST‐1 on electrospun cellulose nanofibers. Two different methods for introducing carboxyl groups on the nanofiber surface were used; HKUST‐1 was then synthesized on the cellulose nanofiber surface using a layer‐by‐layer approach. The distribution of HKUST‐1 on the nanofiber surface was highly dependent on the type of anionic pretreatment. The loading of HKUST‐1 on the nanofiber surface could be controlled by the layer‐by‐layer synthesis and the BET surface area could be increased by a factor of 44 to 440 m2 g−1.